Influence mechanism of thermoelectric coupling on microstructure of aluminum/steel continuous drive friction welding joints - ZHANG Changqing; WANG Shuwen; LUO Dechun; SHI Wenchen; LIU Xiao; CUI Guosheng; CHEN Boyang; XIN Zhou; RUI Zhiyuan (Cailiao gongcheng, 2022)
Continuous drive friction welding technology was used to weld pure aluminum 1060/Q235 low carbon steel dissimilar material joints, and two cycles (30 d/60 d) thermoelectric coupling test (static load 392 N +high temperature 300 ℃+DC 60 A) was carried out. The effect of thermoelectric coupling on the microstructure, mechanical properties and interface growth of the welded joints of aluminum/steel dissimilar materials was studied. The results show that the thickness of the intermetallic compounds (IMCs) layer in the radial direction of the original joint interface is uneven, and there is no obvious IMCs formation in the central area. After 30 days of thermoelectric coupling, an IMCs layer with a width of 0.3-0.5 μm at the center of the interface is formed and dispersed from the steel side to the aluminum side in granular form, the overall tensile fracture is in the thermally affected zone of the aluminum base metal. After 60 days of thermoelectric coupling, a corrosion groove appears between the IMCs layer and the steel side, and the IMCs are broken, there are no cracks on the steel side, a large number of cracks and voids from the IMCs layer to the aluminum base metal are formed on the aluminum side, segregation of components occurs at the weld and crack tip, the overall tensile fracture is at the weld. The speed of interfacial corrosion and failure rate is proportional to the thickness of the interface IMCs layer, namely vcenter < v1/2R < v2/3R. Due to the uneven structure of the original joint interface and the difference in the growth rate of the structure at different positions of the interface during the thermoelectric coupling test, the boundary line of different fracture morphologies appears at the 2/3R position of the joint interface after thermoelectric coupling. The inner side of 2/3R is dominated by quasi-cleavage fracture, and the outer side of 2/3R is the combined result of dimple fracture and quasi-cleavage fracture.